2023
DOI: 10.1177/21582440221149717
|View full text |Cite
|
Sign up to set email alerts
|

Inventory Management and Pharmaceutical Supply Chain Performance of Hospital Pharmacies in Bahrain: A Structural Equation Modeling Approach

Abstract: The ultimate goal of healthcare systems is to offer care and the right treatment to patients. To achieve it, Pharmaceutical Supply Chain (PSC) in the healthcare system needs to be effective and efficient. This study aims to investigate the role of inventory level control and demand forecasting on PSC performance of hospital pharmacies. Data was collected from 171 respondents working in private hospitals in Bahrain using a survey questionnaire and was analyzed using a structural equation modeling approach. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…This investigation in the centre of Peninsular Malaysia revealed a significant relationship between fish species and mortality rates, specifically on Patin fish. This aligns with findings from George and Elrashid (2023) and Nwaiku and Ejechi (2022), who noted varying susceptibilities of different fish species to environmental stressors, impacting survival rates. However, studies by Salleh et al (2022) and Irwanda et al (2022) showed no significant mortality differences among fish species in polluted environments.…”
Section: Coefficientsupporting
confidence: 90%
“…This investigation in the centre of Peninsular Malaysia revealed a significant relationship between fish species and mortality rates, specifically on Patin fish. This aligns with findings from George and Elrashid (2023) and Nwaiku and Ejechi (2022), who noted varying susceptibilities of different fish species to environmental stressors, impacting survival rates. However, studies by Salleh et al (2022) and Irwanda et al (2022) showed no significant mortality differences among fish species in polluted environments.…”
Section: Coefficientsupporting
confidence: 90%
“…Existing research [20] emphasizes the critical role of SOPs in ensuring consistent and safe dispensing practices. Recommendations include the urgent implementation of SOPs, training programs for dispensing staff, and the adoption of standardized labelling practices.…”
Section: Discussionmentioning
confidence: 99%
“…Tasnim et al [28] and George and Elrashid [29] explored the significance of strategic supply chain drivers in disaster management practices, such as pricing, inventory management, transportation, information, and sourcing. Effective inventory management and demand forecasting practices were highlighted as crucial for enhancing supply chain competence in organizations.…”
Section: The Literature Reviewmentioning
confidence: 99%